Competence of the STF: the STF violates the principle of the natural judge in judgments relating to the acts of 8/1 - Xavier, Déborah Pereira Soares; Oliveira, Enio Walcacer de (JRG Journal of Academic Studies, 2024)
The Federal Supreme Court – STF acts mainly to protect the 1988 Federal Constitution, thus acting in cases of constitutionality and unconstitutionality, as well as serving as the last instance of appeal. Therefore, this article aims to examine the role of the Federal Supreme Court in judgments relating to the acts of 8/1, aiming, above all, to reflect on the violation (or not) of the principle of the Natural Judge. It is worth mentioning that the aim is to provide a non-exhaustive analysis on the topic, as the subject is broad, making it impossible to exhaust all resources on the subject. To make the study viable, the deductive method was adopted and the sources are predominantly bibliographic, based on specialized magazines, books and scientific articles. To this end, the study is structured around three basic points: firstly, it concerns the jurisdiction of the Federal Supreme Court in the 1988 Constitution; on a second level, the principle of the Natural Judge is approached and as a third and final topic, the principle analysis regarding the competence of the STF in judgments relating to the acts of 8/1 is discussed.